Von Willebrand factor assays in patients with acquired immune thrombotic thrombocytopenia purpura treated with caplacizumab. (8th March 2022) - Bowyer, Annette; Brown, Paula; Hopkins, Barbara; Scully, Marie; Shepherd, Fiona; Lowe, Anna; Mensah, Patrick; Maclean, Rhona; Kitchen, Steve; van Veen, Joost J.
Abstract: Acquired immune thrombotic thrombocytopenic purpura (iTTP) is a rare disease with a poor prognosis if undiagnosed. It is caused by autoantibody production to the von Willebrand factor (VWF) cleaving protease, A disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13). Caplacizumab, an immunoglobulin directed to the platelet glycoprotein Ibα receptor of VWF, has been reported to induce quicker resolution of iTTP compared to placebo. The laboratory measurement of VWF activity was significantly reduced in clinical trials of caplacizumab. Several VWF assays are available in the UK and this study investigated whether differences in VWF parameters were present in 11 patients diagnosed with iTTP and treated with daily caplacizumab. Chromogenic factor VIII activity, VWF antigen, collagen binding activity, VWF multimers and six VWF activity assays were measured prior to caplacizumab therapy and on several occasions during treatment. VWF antigen and collagen binding activity levels were normal or borderline normal in all patients. Ultra‐large molecular weight multimers were present in all patients following treatment. VWF activity assays were normal or reduced during treatment, but this was reagent and patient dependant. In the unusual scenario of a caplacizumab‐treated patient requiring measurement of VWF activity, it is important that laboratories understand how their local reagents perform as results cannot be predicted.